Inertia–Acoustophoresis Hybrid Microfluidic Device for Rapid and Efficient Cell Separation - Uihwan Kim; Byeolnim Oh; Jiyeon Ahn; Sangwook Lee; Younghak Cho (Sensors, 2022)
In this paper, we proposed an integrated microfluidic device that could demonstrate the non-contact, label-free separation of particles and cells through the combination of inertial microfluidics and acoustophoresis. The proposed device integrated two microfluidic chips which were a PDMS channel chip on top of the silicon-based acoustofluidic chip. The PDMS chip worked by prefocusing the particles/cells through inducing the inertial force of the channel structure. The connected acoustofluidic chips separated particles based on their size through an acoustic radiation force. In the serpentine-shaped PDMS chip, particles formed two lines focusing in the channel, and a trifugal-shaped acoustofluidic chip displaced and separated particles, in which larger particles focused on the central channel and smaller ones moved to the side channels. The simultaneous fluidic works allowed high-efficiency particle separation. Using this novel acoustofluidic device with an inertial microchannel, the separation of particles and cells based on their size was presented and analyzed, and the efficiency of the device was shown. The device demonstrated excellent separation performance with a high recovery ratio (up to 96.3%), separation efficiency (up to 99%), and high volume rate (>100 µL/min). Our results showed that integrated devices could be a viable alternative to current cell separation based on their low cost, reduced sample consumption and high throughput capability.